S-Asymptotically Bloch Type Periodic Solutions for Abstract Fractional Equations Involving psi -Hilfer Derivatives - Chegloufa, Naceur; Chaouchi, Belkacem; Boutaous, Fatiha; Kosti'c, Marko (Journal of Applied Nonlinear Dynamics, 2026)
The aim of this work is to investigate the existence and uniqueness of S-asymptotically Bloch type periodic solutions for a class of the neutral ψ -Hilfer fractional derivative equations with infinite delay. Our approach is based on the semigroup theory. In the end, we present an example to illustrate the applications of the abstract results.